A Review of the Spiritual Marketing Model in the Context of Religion, Culture, and Organization - Ridwan Baidlowi (Yayasan Ilomata, 2026)
Spiritual marketing is an alternative approach in marketing science that emphasizes the importance of religious values, culture and organizational spirituality in shaping the relationship between companies and consumers. This study aims to review related literature and develop a conceptual model of spiritual marketing that integrates three main dimensions: religious values as the source of ethical norms, local culture as the symbolic framework, and spiritual values in the organization as the operational foundation. Using the Stimulus-Organism-Response (S-O-R) framework, the study maps how these three elements act as a stimulus that shapes consumers' perceptions and emotional attachments, which in turn drive meaningful purchase decisions. This conceptual approach offers a theoretical contribution in expanding the scope of value-based marketing, as well as providing practical guidance for organizations looking to build authentic and sustainable brand loyalty. The study also recommends further research directions based on quantitative and qualitative approaches to test the validity of the proposed model in various social and cultural contexts.